Functional Connectivity Changes After Initial Treatment With Fingolimod in Multiple Sclerosis - Petsas, Nikolaos; De Giglio, Laura; González-Quintanilla, Vicente; Giuliani, Manuela; De Angelis, Floriana; Tona, Francesca; Carmellini, Maurizio; Mainero, Caterina; Pozzilli, Carlo; Pantano, Patrizia (Frontiers in Neurology, 2019)
On the basis of recent functional MRI studies, Multiple Sclerosis (MS) has been interpreted as a multisystem disconnection syndrome. Compared to normal subjects MS patients show alterations in functional connectivity (FC). However, the mechanisms underlying these alterations are still debated. The aim of the study is to investigate resting state (RS)-FC changes after an initial treatment with fingolimod, a proved anti-inflammatory and immunomodulating agent for MS. We studied 32 right-handed relapsing-remitting MS patients (median Expanded Disability Status Scale: 2.0, mean disease duration: 8.8 years) who underwent both functional and conventional MRI with a 3T magnet. All assessments were performed 3 weeks before starting fingolimod, then, at therapy start and at month 6. Each imaging session included scans at baseline (run1) and after (run2) a 25-minute, within-session, motor-practice task, consisting in a paced right-thumb flexion. FC was assessed using a seed on the left primary motor cortex to obtain parametric maps at run1 and post-task (run2-run1). Comparison between 3-week before- and fingolimod start sessions accounted for a test-retest effect. Main outcome was changes in both baseline and post-task induced connectivity between start and 6 months. MRI contrast enhancement was detected in 14 patients at start and only in 3 at month 6. There was a significant improvement (p < 0.05) in cognitive function, as measured by the Paced Auditory Serial Addition Task, at month 6 compared to start. After accounting for test-retest effect, baseline RS-FC significantly decreased at month 6, with respect to start (p < 0.05, family-wise error corrected) in bilateral occipito-parietal areas and cerebellum. Post-task RS-FC at month 6 showed a significant increment in all examined sessions, involving not only areas of the sensorimotor network, but also posterior cortical areas (cuneus and precuneus) and areas of the prefrontal and temporal cortices (p < 0.05, family-wise error corrected). Cognitive improvement at month 6 was significantly (p < 0.05) related to baseline RS-FC reduction in posterior cortical areas. This study shows significant changes in functional connectivity both at baseline and after the execution of a simple motor task following 6 months of fingolimod therapy.